Impact of Air Traffic Volume on Air Traffic Controllers’ Decision-Making in the Jakarta Control Zone at Perum LPPNPI JATSC - Romi Yoserizal; Rahmawati Sukra; Lina Rosmayanti (CV. AFDIFAL MAJU BERKAH, 2026)
Air transportation is an essential element in strengthening regional connectivity and driving national economic growth. The rise in aircraft movements at Soekarno-Hatta International Airport following the COVID-19 pandemic has increased the complexity of air traffic management, particularly within the Jakarta Control Zone overseen by the Perum LPPNPI JATSC Branch. In this demanding environment, air traffic controllers (ATCs) must make rapid and accurate decisions to ensure flight safety and operational efficiency. This study examines the impact of traffic volume on ATC decision-making quality in the Jakarta Control Zone. Using a quantitative survey approach, data were collected from 71 randomly selected respondents out of 188 ATC personnel through observation, documentation, and questionnaires. The data were analyzed using SPSS version 25, employing Pearson correlation and simple linear regression tests. The results indicate a strong positive correlation between traffic volume and decision-making quality, showing that higher traffic density increases workload and reduces decision accuracy. The study concludes that effective airspace sector management requires revising sector divisions and updating AIRAC AIP AMDT documentation to align with current operational demands and maintain air traffic safety and efficiency.